A composite lithium sulfide positive electrode material and its preparation method and application

By using nickel nitride and iron nitride as dual catalysts and nitrogen-doped multi-stage porous carbon as support in lithium-sulfur batteries, the problems of low sulfur utilization and serious shuttle effect in lithium-sulfur batteries are solved, and high energy density and good cycle stability are achieved.

CN119252909BActive Publication Date: 2025-04-04SHANDONG HAIHUA GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411775092.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The utilization rate of sulfur in lithium-sulfur batteries is not high and the shuttle effect is severe. In actual applications, existing conductive nanomaterials require additional conductive agents, resulting in reduced energy density and insufficient electron and ion conductivity, which affects Coulomb efficiency and cycle life.

Method used

Nickel nitride and iron nitride are used as dual catalysts to synergistically accelerate the oxidation reaction of lithium sulfide and slow down the dissolution and migration of polysulfides; nitrogen-doped multi-stage porous carbon supports long-chain lithium sulfide, alleviate the volume expansion problem, and capture polysulfides through polar interactions.

Benefits of technology

It significantly improves the initial specific capacity and cyclic stability of lithium sulfur batteries, reduces the shuttle effect, and ensures uniform deposition of lithium sulfide and improves the kinetics of electrochemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252909B_ABST
    Figure CN119252909B_ABST
Patent Text Reader

Abstract

The invention discloses a composite lithium sulfide positive electrode material and a preparation method and application thereof, and belongs to the field of lithium-sulfur batteries. The invention uses a one-step calcination method of a carbon source and a metal salt, and reacts urea with a nickel salt and an iron salt to generate a nickel nitride and iron nitride complex, and glucose and urea generate nitrogen-doped multi-level porous carbon under the action of a sodium chloride template, thereby obtaining a nickel nitride / iron nitride complex and a nitrogen-doped multi-level porous carbon composite material as a precursor material. Lithium sulfide is mixed with N-methylpyrrolidone to prepare a lithium sulfide slurry. The prepared precursor material is immersed in the lithium sulfide slurry and dried to obtain a composite lithium sulfide positive electrode material. In the material, nickel nitride and iron nitride act as dual catalysts, and the synergistic effect accelerates the redox reaction of lithium sulfide / lithium polysulfide. In addition, the nitrogen-doped multi-level porous carbon structure can effectively carry lithium sulfide and lithium polysulfide, and alleviate volume expansion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-sulfur batteries, and in particular relates to a composite lithium sulfide positive electrode material and a preparation method and application thereof. Background Art

[0002] As current lithium-ion batteries approach the theoretical upper limit of their energy density, the market demand for new rechargeable battery systems that can provide higher energy density is growing. Lithium-sulfur batteries have attracted much attention for their ultra-high theoretical specific capacity (up to 1675mAh / g) and are regarded as the leader in future electrochemical energy storage devices. Despite this, in the actual application of lithium-sulfur batteries, they still face challenges such as low sulfur utilization and shuttle effect. These problems mainly stem from the poor electronic conductivity of sulfur species and the easy dissolution of intermediate long-chain polysulfides produced during the positive electrode reaction. In response to the challenges in lithium-sulfur batteries, previous work has mostly focused on designing various conductive nanomaterials as effective sulfur hosts to improve battery performance. However, these sulfur hosts usually require additional auxiliary materials such as conductive agents in practical applications, and the use of these additives will inevitably reduce the energy density of the battery.

[0003] Compared with sulfur (2.07 g / cm 3 ), lithium sulfide has a lower volume mass density (1.66g / cm 3 ), which allows lithium sulfide to effectively reduce the volume expansion problem of sulfur active substances in the initial stage of battery cycle and reduce the pulverization phenomenon of positive electrode materials caused by volume change. However, current research often ignores the electronic and ionic conductivity of lithium sulfide, which leads to a series of performance problems such as reduced Coulomb efficiency and shortened cycle life of lithium-sulfur batteries. The Chinese patent document with publication number CN106876698A discloses a method for preparing a positive electrode material for a lithium-sulfur battery, which is coated with lithium sulfide by an infinite coordination polymer to generate a coated product, and the lithium sulfide positive electrode material generated by the coated product is post-treated. The infinite coordination polymer is not only used as a coating agent but also as a precursor to obtain carbon, metal and metal oxide materials with high conductivity and adsorption properties after post-treatment, thereby improving the overall performance of the battery. However, the positive electrode material fails to provide a rich specific surface area, which limits the contact area between the active material and the electrolyte, thereby affecting the charge and discharge efficiency of the battery; secondly, the non-polar carbon material can only provide weak physical constraints on the polar lithium polysulfide, thereby affecting the cycle life and stability of the battery. Summary of the invention

[0004] The purpose of the present invention is to provide a composite lithium sulfide positive electrode material and its preparation method and application. Nickel nitride and iron nitride are used as dual catalysts, and their synergistic effect is to accelerate the oxidation reaction of lithium sulfide and effectively slow down the dissolution and migration of polysulfides in the electrolyte; nitrogen-doped multi-level porous carbon can effectively carry long-chain lithium polysulfide and alleviate the volume expansion problem of sulfur active substances. At the same time, nitrogen doping has a certain catalytic activity, which will help improve the electrochemical reaction kinetics; it can not only improve the initial specific capacity of the battery, but also significantly improve the cycle stability of the battery.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a composite lithium sulfide positive electrode material, comprising the following steps:

[0007] (1) Adding glucose, urea, sodium chloride, nickel salt and iron salt into deionized water to prepare a mixed solution;

[0008] (2) removing moisture from the mixed solution obtained in step (1) by freeze drying, then calcining at high temperature under a protective atmosphere, cooling to room temperature, and washing with deionized water to obtain a precursor material;

[0009] (3) adding lithium sulfide into N-methylpyrrolidone and stirring to prepare lithium sulfide slurry;

[0010] (4) The lithium sulfide slurry obtained in step (3) is added dropwise to the precursor material obtained in step (2), ground into a viscous state, and then vacuum dried to obtain a composite lithium sulfide positive electrode material.

[0011] Preferably, in the mixed solution of step (1), the mass ratio of urea to glucose and sodium chloride is 1:1-5:5-10, the mass ratio of nickel salt to iron salt is 1:1-10, the nickel salt is one of nickel nitrate, nickel sulfate or nickel chloride; the iron salt is one of iron nitrate, iron sulfate or iron chloride; the mass concentration of glucose is 0.05-0.25 g / ml, and the mass concentration of iron salt is 0.02-0.03 g / mL.

[0012] Preferably, in step (2), the freeze-drying temperature is -50 to -65°C, and the time is 12 to 24 hours; the protective atmosphere is nitrogen or argon, the calcination temperature is controlled at a rate of 2 to 10°C / min, the calcination temperature is 700 to 900°C, and the time is 1 to 5 hours.

[0013] Preferably, in step (3), the concentration of lithium sulfide in N-methylpyrrolidone is 50-100 mg / mL.

[0014] Preferably, in step (4), the vacuum drying temperature is 60 to 80° C. and the time is 4 to 8 hours.

[0015] In a second aspect, the present invention provides a composite lithium sulfide positive electrode material, which includes lithium sulfide crystals, nickel nitride / iron nitride composites and nitrogen-doped multilevel porous carbon, wherein the lithium sulfide crystals and the nickel nitride / iron nitride composites are embedded in the nitrogen-doped multilevel porous carbon, wherein the lithium sulfide crystals account for 40.5 to 68.1% of the mass of the positive electrode material, the nickel nitride accounts for 1.4 to 5.6% of the mass of the positive electrode material, and the iron nitride accounts for 2.9 to 9.0% of the mass of the positive electrode material.

[0016] In a third aspect, there is also provided an application of the composite lithium sulfide positive electrode material prepared by the present invention for use in a lithium-sulfur battery positive electrode.

[0017] The beneficial effects of the present invention are as follows:

[0018] 1. The present invention uses a one-step calcination method of carbon source and metal salt to make urea react with nickel salt and iron salt to generate nickel nitride and iron nitride complexes, and glucose and urea generate nitrogen-doped multi-level porous carbon under the action of sodium chloride template to obtain nickel nitride / iron nitride complexes and nitrogen-doped multi-level porous carbon composite materials. The method is simple and easy to implement, and the additional nitridation step is abandoned. The composite lithium sulfide positive electrode material prepared by the present invention can effectively load a large amount of active material lithium sulfide and load it evenly due to the porosity of nitrogen-doped multi-level porous carbon. The introduction of a small amount of nickel nitride / iron nitride composite can improve the battery energy density to a certain extent on the one hand, and can effectively capture and anchor polysulfides through polar interactions on the other hand, thereby effectively inhibiting the common shuttle effect in lithium-sulfur batteries; nickel nitride and iron nitride act as dual catalysts, catalyzing the oxidation reaction of lithium sulfide and the subsequent redox reaction of polysulfides in the solid-liquid-solid conversion reaction of lithium sulfide in lithium-sulfur batteries, effectively slowing down the dissolution and migration of polysulfides in the electrolyte, ensuring the uniform deposition of lithium sulfide on the surface of the positive electrode material, and inhibiting the generation of dead sulfur (sulfur that does not participate in the electrochemical reaction). Through this dual catalyst strategy, not only the initial specific capacity of the battery is improved, but also the cycle stability of the battery is significantly improved. The nitrogen-doped multi-level porous carbon prepared by the present invention has certain adsorption and catalytic activity, which has a positive effect on the electrochemical redox reaction in the lithium-sulfur battery, can have a strong chemical interaction with lithium sulfide / lithium polysulfide, helps to improve the electrochemical reaction kinetics, and reduce the dissolution and shuttling of lithium polysulfide in the electrolyte, thereby improving the cycle stability of the battery.

[0019] 2. The composite lithium sulfide cathode material prepared by the present invention performs outstandingly in lithium-sulfur battery applications. Under 1C conditions, the initial specific capacity is as high as 880.4-893.6 mAh / g, and the capacity retention rate is 79.1%-81.7% in 200 cycle tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope (SEM) image of the composite lithium sulfide positive electrode material prepared in Example 1;

[0021] Figure 2 This is a magnified SEM image of the composite lithium sulfide positive electrode material prepared in Example 1;

[0022] Figure 3 Element distribution diagram of carbon, sulfur, nitrogen, iron and nickel in the composite lithium sulfide positive electrode material prepared in Example 1;

[0023] Figure 4 The X-ray diffraction (XRD) pattern of the composite lithium sulfide positive electrode material prepared in Example 1;

[0024] Figure 5 The cycle stability of the composite lithium sulfide positive electrode material prepared in Example 1 at 1C. DETAILED DESCRIPTION

[0025] The present invention is described in detail below with reference to the embodiments and comparative examples, but the present invention is not limited thereto. Example 1

[0026] (1) Add 1 g of glucose, 1 g of urea, 10 g of sodium chloride, 0.08 g of nickel nitrate and 0.4 g of iron nitrate into 20 ml of deionized water to prepare a mixed solution;

[0027] (2) removing moisture from the mixed solution obtained in step (1) by freeze drying at a freeze drying temperature of -65°C for 24 hours, then heating to 900°C at a heating rate of 5°C / min under a nitrogen atmosphere and keeping the temperature for 1 hour, cooling to room temperature and washing with deionized water to obtain a precursor material;

[0028] (3) Add 60 mg of lithium sulfide into 1 ml of N-methylpyrrolidone and stir to prepare lithium sulfide slurry;

[0029] (4) The lithium sulfide slurry is added dropwise to the precursor material, ground into a viscous state, and then placed in a vacuum oven at 80°C for 4 hours to obtain a composite lithium sulfide positive electrode material.

[0030] The composite lithium sulfide positive electrode material obtained in this embodiment includes lithium sulfide crystals, nickel nitride / iron nitride composites and nitrogen-doped multi-level porous carbon. The lithium sulfide crystals and the nickel nitride / iron nitride composites are embedded in the nitrogen-doped multi-level porous carbon. The lithium sulfide crystals account for 46.9% of the mass of the positive electrode material, the nickel nitride accounts for 1.4% of the mass of the positive electrode material, and the iron nitride accounts for 2.9% of the mass of the positive electrode material. Example 2

[0031] (1) Add 5 g of glucose, 1 g of urea, 10 g of sodium chloride, 0.5 g of nickel sulfate and 0.5 g of ferric chloride to 20 ml of deionized water to prepare a mixed solution;

[0032] (2) removing moisture from the mixed solution obtained in step (1) by freeze drying at a freeze drying temperature of -50°C for 20 hours, then heating to 700°C at a heating rate of 2°C / min under an argon atmosphere and keeping the temperature for 2 hours, cooling to room temperature and washing with deionized water to obtain a precursor material;

[0033] (3) Add 100 mg of lithium sulfide into 1 ml of N-methylpyrrolidone and stir to prepare lithium sulfide slurry;

[0034] (4) The lithium sulfide slurry is added dropwise to the precursor material, ground into a viscous state, and then placed in a vacuum oven at 60°C for 8 hours to obtain a composite lithium sulfide positive electrode material.

[0035] The composite lithium sulfide positive electrode material obtained in this embodiment includes lithium sulfide crystals, nickel nitride / iron nitride composites and nitrogen-doped multi-level porous carbon. The lithium sulfide crystals and the nickel nitride / iron nitride composites are embedded in the nitrogen-doped multi-level porous carbon. The lithium sulfide crystals account for 68.1% of the mass of the positive electrode material, the nickel nitride accounts for 5.6% of the mass of the positive electrode material, and the iron nitride accounts for 5.9% of the mass of the positive electrode material. Example 3

[0036] (1) Add 5 g of glucose, 1 g of urea, 5 g of sodium chloride, 0.12 g of nickel chloride and 0.6 g of ferric chloride to 20 ml of deionized water to prepare a mixed solution;

[0037] (2) removing moisture from the mixed solution obtained in step (1) by freeze drying at a freeze drying temperature of -60°C for 12 hours, then heating to 800°C at a heating rate of 10°C / min under an argon atmosphere and keeping the temperature for 5 hours, cooling to room temperature and washing with deionized water to obtain a precursor material;

[0038] (3) Add 50 mg of lithium sulfide into 1 ml of N-methylpyrrolidone and stir to prepare lithium sulfide slurry;

[0039] (4) The lithium sulfide slurry is added dropwise to the precursor material, ground into a viscous state, and then placed in a vacuum oven at 70°C for 6 hours to obtain a composite lithium sulfide positive electrode material.

[0040] The composite lithium sulfide positive electrode material obtained in this embodiment includes lithium sulfide crystals, nickel nitride / iron nitride composites and nitrogen-doped multi-level porous carbon. The lithium sulfide crystals and the nickel nitride / iron nitride composites are embedded in the nitrogen-doped multi-level porous carbon. The lithium sulfide crystals account for 40.5% of the mass of the positive electrode material, the nickel nitride accounts for 4.2% of the mass of the positive electrode material, and the iron nitride accounts for 9.0% of the mass of the positive electrode material. Comparative Example 1

[0041] In this comparative example, no nickel salt is added, and the other processes are consistent with those in Example 1.

[0042] In the composite lithium sulfide positive electrode material obtained in this comparative example, the lithium sulfide crystals account for 47.3% of the mass of the positive electrode material, and the iron nitride accounts for 3.8% of the mass of the positive electrode material. Comparative Example 2

[0043] In this comparative example, no iron salt is added, the mass of nickel nitrate is 0.8 g, and the other processes are consistent with those in Example 1.

[0044] In the composite lithium sulfide positive electrode material obtained in this comparative example, the lithium sulfide crystals account for 46.9% of the mass of the positive electrode material, and the nickel nitride accounts for 4.5% of the mass of the positive electrode material.

[0045] Performance Testing:

[0046] The prepared lithium sulfide @Ni3N-Fe2N / N-HPC positive electrode material is mixed with Super-P (conductive agent) and PVDF (binder) in an N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:1, and stirred thoroughly to form a uniform slurry. Subsequently, the slurry is evenly coated on the surface of aluminum foil to prepare the positive electrode of the lithium-sulfur battery. Next, Celgard2300 is selected as the battery separator, and lithium foil is used as the negative electrode material, and assembled with the electrolyte (a solution composed of 1.0 mol / L LiTFSI, 0.2 mol / L LiNO3, and 1,3-dioxolane and 1,2-dimethoxyethane in a volume ratio of 1:1) to prepare a C2032 button battery. On the CT-4008-5A6V system, the battery was tested at a fixed potential range (1.7-2.8Vvs.Li + / Li) to perform a cycle test on the battery. The test current density is 1C, and the test results are shown in Table 1:

[0047]

[0048] Figure 1 and 2This is a SEM image of the positive electrode material of the lithium-sulfur battery prepared in Example 1. A composite lithium sulfide positive electrode material is composed of lithium sulfide crystals embedded in N-doped multi-level porous carbon of a nickel nitride and iron nitride composite. The surface of the positive electrode material is rough, and a large number of lithium sulfide crystals are evenly fixed on the surface of N-HPC. The elemental composition and distribution of the lithium sulfide @Ni3N-Fe2N / N-HPC positive electrode material prepared in Example 1 were analyzed in detail using an energy dispersive X-ray spectrometer (EDS). The corresponding EDS element distribution map is shown in Figure 3 From the analysis results, five elements, carbon, sulfur, nitrogen, iron and nickel, were detected in the positive electrode material. Among them, sulfur comes from lithium sulfide. Its uniform distribution in the positive electrode material indicates that the lithium sulfide crystals are well dispersed in the entire positive electrode material. This uniform dispersion effect is due to the composite pore structure of N-HPC, which has micropores, mesopores and macropores, which can effectively carry long-chain lithium polysulfides and alleviate the volume expansion problem of lithium sulfide during lithiation and delithiation. This multi-level pore structure not only provides sufficient space for lithium sulfide to adapt to its volume change, but also promotes the rapid transmission of electrons and lithium ions, thereby improving the charge and discharge efficiency of the battery. Figure 3 The doping of nitrogen in HPC gives it a certain adsorption and catalytic activity, which has a positive effect on the electrochemical redox reaction in lithium-sulfur batteries. It can have a strong chemical interaction with lithium sulfide / lithium polysulfide, which helps to improve the electrochemical reaction kinetics and reduce the dissolution and shuttling of lithium polysulfide in the electrolyte, thereby improving the coulombic efficiency and cycle stability of the battery.

[0049] The positive electrode material obtained in Example 1 was subjected to XRD test. Figure 4 As shown. It can be observed from the figure that a broad peak appears at about 20°, which indicates the presence of N-HPC; in addition, a series of sharp diffraction peaks appear in the figure, which match the standard peaks of Ni3N, Fe2N and lithium sulfide, respectively. This result verifies the successful synthesis of the positive electrode material of lithium-sulfur battery. Among the prepared positive electrode materials, Ni3N and Fe2N have attracted much attention due to their low cost, excellent electronic conductivity and stable structural characteristics. These two materials effectively capture and fix polysulfides through their polar forces, effectively reducing the shuttle effect that is prevalent in lithium-sulfur batteries. Furthermore, Ni3N and Fe2N, as a dual catalytic system, play a key role in the solid-liquid-solid transformation of lithium sulfide in lithium-sulfur batteries. This dual catalytic mechanism not only accelerates the oxidation reaction rate of lithium sulfide, but also significantly reduces the dissolution and migration of polysulfides in the electrolyte, ensuring the uniform deposition of lithium sulfide on the surface of the positive electrode material. Through this dual catalyst strategy, not only the initial specific capacity of the battery is improved, but also the cycle stability of the battery is significantly improved.

[0050] The prepared lithium-sulfur battery cathode material was assembled into a lithium-sulfur battery in a glove box and electrochemically tested at 1.7-2.8V and 1C current density. Figure 5 As shown. The initial specific capacity of lithium sulfide @Ni3N-Fe2N / N-HPC prepared in Example 1 is 893.6mAh / g, and the capacity retention rate after 200 cycles reaches 81.7%, showing excellent charge and discharge performance and cycle stability. The same test was performed on the materials of Examples 2 and 3, and the results were similar to those of Example 1 (Table 1). At a current density of 1C, the difference in discharge specific capacity of the samples of each example did not exceed 13.2mAh / g, and the difference in capacity retention rate did not exceed 2.6%.

[0051] Compared with the samples of Comparative Examples 1 and 2, the examples have better performance under 1C conditions, indicating that Ni3N and Fe2N as a dual catalytic system accelerate the oxidation reaction rate of lithium sulfide, and also significantly reduce the dissolution and migration of polysulfides in the electrolyte, thereby enhancing the charge and discharge capacity and cycle stability of the battery (Table 1).

[0052] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite lithium sulfide positive electrode material, characterized in that: The steps include: (1) Adding glucose, urea, sodium chloride, nickel salt and iron salt into deionized water to prepare a mixed solution; (2) removing moisture from the mixed solution obtained in step (1) by freeze drying, then calcining at high temperature under a protective atmosphere, cooling to room temperature, and washing with deionized water to obtain a precursor material; (3) adding lithium sulfide into N-methylpyrrolidone and stirring to prepare lithium sulfide slurry; (4) adding the lithium sulfide slurry obtained in step (3) dropwise to the precursor material obtained in step (2), grinding into a viscous state, and vacuum drying to obtain a composite lithium sulfide positive electrode material; In the mixed solution of step (1), the mass ratio of urea to glucose and sodium chloride is 1:1-5:5-10, the mass ratio of nickel salt to iron salt is 1:1-10, the nickel salt is one of nickel nitrate, nickel sulfate or nickel chloride; the iron salt is one of iron nitrate, iron sulfate or iron chloride; the mass concentration of glucose is 0.05-0.25 g / mL, and the mass concentration of iron salt is 0.02-0.03 g / mL.

2. The method for preparing the composite lithium sulfide positive electrode material according to claim 1, characterized in that: In the step (2), the freeze-drying temperature is -50 to -65°C, and the time is 12 to 24 hours; the protective atmosphere is nitrogen or argon, the calcination temperature is controlled at a rate of 2 to 10°C / min, the calcination temperature is 700 to 900°C, and the time is 1 to 5 hours.

3. The method for preparing the composite lithium sulfide positive electrode material according to claim 1, characterized in that: In the step (3), the concentration of lithium sulfide in N-methylpyrrolidone is 50 to 100 mg / mL.

4. The method for preparing the composite lithium sulfide positive electrode material according to claim 1, characterized in that: In the step (4), the vacuum drying temperature is 60 to 80° C. and the time is 4 to 8 hours.

5. A composite lithium sulfide positive electrode material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The composite lithium sulfide positive electrode material includes lithium sulfide crystals, nickel nitride / iron nitride composites and nitrogen-doped multi-level porous carbon. The lithium sulfide crystals and the nickel nitride / iron nitride composites are embedded in the nitrogen-doped multi-level porous carbon. The lithium sulfide crystals account for 40.5-68.1% of the mass of the positive electrode material, the nickel nitride accounts for 1.4-5.6% of the mass of the positive electrode material, and the iron nitride accounts for 2.9-9.0% of the mass of the positive electrode material.

6. An application of the composite lithium sulfide positive electrode material as claimed in claim 5, characterized in that: The composite lithium sulfide positive electrode material is used for the positive electrode of a lithium-sulfur battery.

Citation Information

Patent Citations

  • Positive electrode material of lithium-sulfur battery and preparation method and application of positive electrode material

    CN106876698A

  • Lithium ion battery negative electrode material and preparation method of lithium sulfide battery

    CN105428634A

  • Lithium sulfide battery positive electrode material and preparation method thereof

    CN115775882A